Naimark-Sacker bifurcations in linearly coupled quadratic maps - Rech P.C.* (2004)
We report exact analytical expressions locating the 0 → 1, 1 → 2 and 2 → 4 bifurcation curves for a prototypical system of two linearly coupled quadratic maps. Of interest is the precise location of the parameter sets where Naimark-Sacker bifurcations occur, starting from a non-diagonal period-2 orbit. This result is the key to understand the onset of synchronization in networks of quadratic maps. © 2004 Elsevier B.V. All rights reserved.